IMPROVING STUDENTS’ ABILITY IN WRITING HORTATORY EXPOSITION TEXT BY USING RAFT STRATEGY - Yuniarti, Fransiska; Marbun, Rismaya; Suhartono, Luwandi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2015)
Abstract: This research is concerned with finding how well RAFT strategy improved students’ hortatory exposition text writing skill in terms of correctness of writing simple present tense and writing complete text organization of hortatory exposition text. The purpose is to improve students’ ability in writing hortatory exposition text. The method of this research was classroom action research. The subjects of this research were 32 students at the second semester of the eleventh grade students of SMAN 7 Pontianak in academic year 2013/2014. Based on the data analysis, the result of the research was progress. It is showed that the students’ mean score for writing hortatory exposition improved from 69.63 (average) in the first cycle to 79.90 (good) in the second cycle. Based on the result of the data analysis, the writer took a conclusion that RAFT strategy is work well in improving students’ ability in writing hortatory exposition text.   Keywords: RAFT strategy, hortatory exposition text, writing     Abstrak: penelitian ini merupakan penelitian mengenai penemuan seberapa baik strategi RAFT meningkatkan keterampilan menulis text hortatory siswa dalam hubungan kebenaran menulis tenses simple present dan teks organisasi yang lengkap dari teks hortatory eksposisi. Tujuan dari penelitian ini adalah untuk meningkatkan kemampuan siswa dalam menulis teks hortatory eksposisi. Metode yang digunakan adalah penelitian tindakan kelas. Subjek dari penelitian ini adalah 32 orang siswa kelas XI IPA semester 2 dari SMAN 7 Pontianak tahun akademik 2013/2014. Berdasarkan data analisis, hasilnya menunjukkan peningkatan. Hal tersebut dibuktikan dari nilai rata-rata siswa dalam menulis teks hortatory eksposisi yang meningkat dari 69.63(sedang) di lingkaran pertama menjadi 79.90 (baik) dilingkaran kedua. Berdasarkan hasil data analisis, penulis mengambil kesimpulan bahwa strategi RAFT bekerja dengan baik dalam meningkatkan kemampuan menulis siswa dalam teks hortatory eksposisi. Kata kunci: Strategi RAFT, teks hortatory eksposisi, menulis